The Definition of “Female Style” in Literature - N. Parmonova (Periodica Journal, 2022)
This article is dedicated to that in the Middle Ages, the history of the issue of gender in art actively developed the hatred of women, which was reflected even in literature, and in various types of art. By the twentieth century, feminism in the US and Great Britain already occupies a very strong position in the public consciousness, so the works of many writers are clearly studied from the point of view of their feminism simplicity. It should be noted that everything that is written with a woman's hand does not automatically fall into the definition of “women's literature”. A number of critics point out this kind of female prose, which includes features outside the gender literature. Gender-free literature is considered to be written with a female hand, but does not place itself as a “female”, that is, a “male speech” appears in it.
Keywords: Literature; Consciousness; Literature”; Female